Automated video assistant referee in lead climbing - Künzler, E.; Roder, D.; Stöcker, U.; Wolf, P. (Current Issues in Sport Science, 2025)
Introduction In lead climbing, points are awarded for each hold held, which are then primarily decisive for the ranking. These points are awarded immediately after an attempt by a judge who observed the athlete. Competition organisers are required to make video recordings, but these are only viewed by the head referee in case of an appeal.